(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2022)
In the 21st century where we operate with advanced technological advances where it is impossible to be disconnected and not take work home, making working hours long, make this the ideal environment for Burnout syndrome to appear, which is considered by the world health organization in 2000 as an entity capable of disturbing the health of workers. Methodology: A retrospective and observational work was carried out, to be carried out by surgeons from the departments of general surgery, Traumatology, Neurosurgery and Gynecology, who work at the Abel Gilbert Pontón hospital. The Maslach Burnout Inventory Version Human Services Survey in Spanish was used, which measures emotional fatigue, depersonalization, and low professional performance. Results: Emotional exhaustion was more frequent in 50% of the interviewed general surgeons, depersonalization was present in 58.5% of neurosurgeons, low professional performance was presented in all the interviewed traumatologists. Conclusions: Several factors influence so that the presence of burnout syndrome is present in the professionals surveyed, the most frequent factor is the number of hours worked per week, caring for the patient in the emergency area seems to be an influential factor.